Pertumbuhan Streptococcus alpha 368 Resisten terhadap Multiantibiotik setelah Pemberian Minyak Atsiri Lengkuas Putih in vitro - Susilowati, Heni; Tandelilin, Regina TC (2005)
Antibiotic resistance happened when antibiotic lost its ability to obstruct or eliminate microorganism. Antibiotic resistance causes failure in medication of some infection diseases. Some medication based on essential oil as antibiotic replacement has been developed to deal with this antibiotic resistance problem. The aim of this study was to observe the growth of Streptococcus alpha 368 bacterium after induction using white galangal rhizomes essential oil. This study was conducted based on diffusion method. The test was done 15 times for each sample group and each of the test were divided into PG 5%, and 5, 7.5, 10, 12.5, 15% concentration of essential oil, respectively. Bacterial suspension was added into Blood agar medium then incubated at 37oC for 24 hours. Radical zone diameter was measured three times for each weel using sliding caliper. Kruskal-Wallis analysis showed that there was significant difference between groups (p<0.05). This result indicated that white galangal rhizomes essential oils had some effect to inhibit the growth of S. alpha 368. The Man-Whitney test showed significant differences between the concentrations of essential oil. The 5% concentration showed as the minimum concentration to inhibit the growth of Streptococcus alpha 368.